PWE-092 Will the national awareness and early diagnosis initiative (NAEDI) have an impact on bowel cancer screening activity?. (28th May 2012) - Snowball, J; Young, M; Halloran, S
Abstract : Introduction: 1- and 5-year survival from all cancers in England is poorer than for other comparable countries, largely because of delayed diagnosis. The UK's Department of Health has estimated that if cancer survival in England could be improved to match the best in Europe, then 10 000 lives would be saved every year, about 1700 of which would be from bowel cancer. The National Awareness and Early Diagnosis Initiative (NAEDI) is a Government plan to raise public awareness of the early signs and symptoms of cancer and, as one of the leading causes of cancer death, bowel cancer has been identified as a particular target. During 7 weeks in early 2011, a pilot bowel cancer NAEDI campaign was run in two Strategic Health Authorities (SHAs), including the South West SHA, with widespread coverage on local television, radio and newspapers and distribution of educational literature to general practitioners (GPs). The public was urged to consult their GP if they had any symptoms of bowel cancer and, consequently, attendance with relevant symptoms at GP practices increased by 48% with a 32% increase in 2-week wait referrals. Little direct reference was made to the Bowel Cancer Screening Programme (BCSP). Methods: The BCSP Southern Hub has analysed screening data for the South West SHA to explore the indirect effects of the pilot campaign on screening activity. Screening data for the general practices covered by the media campaign were compared with data for the same practices a year earlier and with data for practices served by the Southern Hub not targeted during the campaign period at that time and a year earlier. Results: There was a small increase in overall uptake among individuals who were participating for the first time, but no evidence of a change in uptake by individuals who had previously participated in the Screening Programme. The Hub saw no increase in the number of calls received by the Helpline, test kits were not returned any more quickly and there was no change in the proportion of positive test kits. Comparisons drawn between the practices described are limited, however, by the likelihood that publicity reached areas not targeted for media coverage, the pilot campaign ran after Christmas when fluctuations in screening activity are considerable and age-extension was underway in some areas. Conclusion: At the end of January 2012, the Government launched a 9-week national bowel cancer awareness campaign. Providers have been urged to plan for a 50% increase in GP referrals during the campaign and for a sustained increase in colonoscopy demand over the next 5 years. This analysis of local screening activity during the pilot campaign, however, suggests that the direct effect of the national NAEDI campaign on bowel cancer screening hub activity is likely to be modest. Competing interests: None declared.